Two-Dimensional FEM Approach of Metabolic Effect on Thermoregulation in Human Dermal Parts During Walking and Marathon - Dev Chandra Shrestha; Saraswati Acharya; Dil Bahadur Gurung (Modelling and Simulation in Engineering)
The physiological mechanisms conduction, convection, and radiation exchange the heat energy in bi-directional routes between the body and the temperature field. Metabolism and evaporation are the uni-directional routes for the exchange of heat energy. In the metabolic process, the body creates internal heat energy, whereas the body loses excess heat energy through the evaporation process and maintains the body temperature. This study has shown steady and unsteady state temperature distribution in three skin layers: epidermis, dermis, and subcutaneous tissue, during walking and marathon. The results have analyzed that each skin layer temperature is higher during a marathon compared with walking due to more metabolic effects. The computation has been carried out for the two-dimensional Pennes’ bio-heat equation using a finite element approach. The generated results have been exhibited graphically.